Health sector reform and reproductive health in Latin America and the Caribbean: strengthening the links - A. Langer; G. Nigenda; J. Catino (The World Health Organization, 2000)
Many countries in Latin America and the Caribbean (LAC) are currently reforming their national health sectors and also implementing a comprehensive approach to reproductive health care. Three regional workshops to explore how health sector reform could improve reproductive health services have revealed the inherently complex, competing, and political nature of health sector reform and reproductive health. The objectives of reproductive health care can run parallel to those of health sector reform in that both are concerned with promoting equitable access to high quality care by means of integrated approaches to primary health care, and by the involvement of the public in setting health sector priorities. However, there is a serious risk that health reforms will be driven mainly by financial and/or political considerations and not by the need to improve the quality of health services as a basic human right. With only limited changes to the health systems in many Latin American and Caribbean countries and a handful of examples of positive progress resulting from reforms, the gap between rhetoric and practice remains wide.